High-temperature behaviour of HVOF (Co, Ni)O coated Cu-Ni-Fe anodes. (15th August 2021) - Mohammadkhani, S.; Jalilvand, V.; Davis, B.; Gauthier, G.H.; Dolatabadi, A.; Moreau, C.; Roué, L.; Guay, D.
Highlights: Single-phase Cox Ni1-x O coatings are deposited by high velocity oxy-fuel spraying. Dense coatings are obtained under optimized deposition conditions. Coating with higher Ni content improves the oxidation resistance of substrates. HVOF-deposited (Co, Ni)O layers are potential coatings for green Al production. Abstract: Cu-Ni-Fe alloys are promising inert anodes for green Al production but their corrosion resistance must be improved. Here, protective (Co, Ni)O coatings are deposited by high velocity oxygen fuel (HVOF) process on Cu-Ni-Fe alloys. The influence of the coating and substrate compositions on their behavior is studied at 1000 °C under argon and air. On Cu-rich alloy, Cox Ni1−x O coatings with higher nickel content slow down oxygen diffusion to the substrate, as well as copper diffusion to the sample surface. On Ni-rich alloy, the formation of a NiFe2 O4 scale is observed, whose thickness decreases as the Ni content of the Cox Ni1−x O coatings increases.